The ideal ear position in Caucasian females. Issue 3 (March 2018) - Broer, P. Niclas; Thiha, Aung; Ehrl, Denis; Sinno, Sammy; Juran, Sabrina; Szpalski, Caroline; Ng, Reuben; Ninkovic, Milomir; Prantl, Lukas; Heidekrueger, Paul I.
Abstract: Purpose: Ear position contributes significantly to facial appearance. However, while objective measurements remain the foundation for esthetic evaluations, little is known about how an ear should ideally be positioned regarding its rotational axis. This study aimed to further evaluate whether there exists a universally applicable ideal ear axis, and how sociodemographic factors impact such preferences. Materials and methods: An interactive online survey was designed, enabling participants to change the axis of a female model's ear in terms of its forward and backward rotation. The questionnaire was sent out internationally to plastic surgeons and the general public. Demographic data were collected and analysis of variance was used to investigate respective preferences. Results: A total of 1016 responses from 35 different countries (response rate: 18.5%) were gathered. Overall, 60% of survey takers chose the minus 10 or 5° angles to be most attractive. Significant differences were found regarding sex, ethnicity, country of residence, profession and respective ear axis preferences. Conclusion: Across multiple countries and ethnicities, an ear position in slight reclination of minus 5–10° is considered most pleasing in Caucasian females. However, sociodemographic factors significantly impact individual ear axis preferences and should be taken into consideration when performing reconstructive ear surgery.